Effect of Phytase Supplementation on the Calcium Requirement of Broiler Chicks - Yan, F.; Kersey, J.H.; Fritts, C.A.; Waldroup, P.W. (International Journal of Poultry Science, 2006)
It has been frequently demonstrated that addition of phytase to corn-soybean meal diets will improve the utilization of the phytate-bound P for the broiler chicken. The effect of phytase on release of other nutrients such as Ca is less clear-cut. A study was conducted to examine the effects of phytase supplementation on diets with various dietary levels of Ca and nonphytate P (nPP). A diet was formulated that provided nutrients in excess of NRC (1994) recommendations with 1.0% Ca and 0.50% nPP. By varying the amounts of dicalcium phosphate, limestone, and sand in aliquots of a common basal diet, diets were prepared with 1) Low-P and Low-Ca, 2) Low-P and High-Ca, 3) High-P and Low-Ca, and 4) High-P and High-Ca. The diets were analyzed for Ca and P content and blended as needed to provide test diets in a factorial arrangement of three Ca levels (0.5, 0.7, and 0.9%) with eight levels of nPP (0.15 to 0.50% in increments of 0.05%). These 24 diets were divided and half supplemented with 1000 units/kg of phytase. Each treatment was fed to six pens of six male broilers from one to 21 d of age. Response of both body weight and tibia ash to phytase supplementation in broilers was significantly affected by dietary Ca levels as well as dietary nPP levels. Without phytase supplementation, both body weight and tibia ash were depressed at the lowest level of nPP as dietary Ca level increased. Adding phytase to these diets improved both body weight and tibia ash as a result of increased availability of P. At both 0.5% and 0.7% Ca, the dietary Ca level was a limiting factor in maximizing tibia ash regardless of P level or phytase supplementation. These data indicate that minimal Ca appeared to be released by phytase and that no reduction in Ca level of broiler should be implemented with phytase supplementation.